Millennial Digital Content Creator on New Normal Era: Factors Explaining Digital Entrepreneur Intention - Ni Putu Santhi Widiasih; Gede Sri Darma (APMBA (Asia Pacific Management and Business Application), 2021)
The impact of Covid-19 pandemic and the new normal era to the intensity of the use of digital media by the millennial generation were significant increased, this condition was in line with the development of the world of work in the industrial era 4.0 where many permanent workers were replaced by freelancers which caused a change in the mindset of the millennial generation toward job preferences that shifted from formal jobs to digital entrepreneurs. This study aimed to determine the factors that influenced digital entrepreneurs' intentions of digital content creators being able to compete in the digital world. Data was collected through 240 experienced digital content creators. Data analysis was performed by SEM-PLS. The findings of this study indicated that self-efficacy was able to strengthen the influence of entrepreneurship education and public support on digital entrepreneur intention. This research leave a gap for further research to examine more detailed which related to the mindset and behavior of the millennial generation towards work preferences in the digital era. Moreover, Indonesia as a nation was predicted to enter an era of surplus population of working productive age and with this research the government could anticipate the early occurrence of job shortages.